Respuesta :
2 − 3 = −5
First we need to Add 3 to both sides of the equation:
2 − 3 + 3 = −5 + 3
Then we simplify:
2 = −5 + 3
2 = −2
Now we divide both sides of the equation by the same term:
2 / 2 = −2 / 2
Final answer: = −1
I hope this helps!
Answer:
Y= - 1
Step-by-step explanation:
2y-3= - 5
+3 +3
2y= -2
/2 /2
Y= -1
Step 1: Add 3 to both sides because you want to cancel out the 3 so you do the opposite of what is say's. For example, if it says 2y-3 add 3 or 2y+3 subtract 3 from both sides.
Step 2: Add 3 to -5 which would be -2
Step 3: Since you're "multiplying" Y to 2 you're going to divide 2 to get Y by itself. So 2/2 cancels out and now you're left with y
Step 4: Divide 2 form -2 and you get -1
Let me know if you have any questions and I hope this helps